2014
DOI: 10.1159/000368002
|View full text |Cite
|
Sign up to set email alerts
|

Focal Lesions in the Cirrhotic Liver: Their Pivotal Role in Gadoxetic Acid-Enhanced MRI and Recognition by the Western Guidelines

Abstract: Hepatocellular carcinoma (HCC) is a major health concern, and early HCC diagnosis is a primary radiological concern. The goal of imaging liver cirrhosis is the early identification of high-grade dysplastic nodules/early HCC since their treatment is associated with a higher chance of radical cure and lower recurrence rates. The newly introduced MRI contrast agent gadoxetic acid (gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid, Gd-EOB-DTPA) has enabled the concurrent assessment of tumor vascularity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 56 publications
0
43
1
2
Order By: Relevance
“…and malignant parotid lesions (4,(13)(14)(15)(16). However, recent studies have demonstrated a comparable high sensitivity and specificity between these imaging modalities (7,17,18).…”
Section: A B Cmentioning
confidence: 99%
“…and malignant parotid lesions (4,(13)(14)(15)(16). However, recent studies have demonstrated a comparable high sensitivity and specificity between these imaging modalities (7,17,18).…”
Section: A B Cmentioning
confidence: 99%
“…Despite these limits several researches have demonstrated that EOB-GD-DTPA can favor the detection and the characterization of HCC nodule [5056]. According to Golfieri et al [53], during the hepatospecific phase, typical HCC and early HCC appear hypointense, whereas low-grade dysplastic or regenerative nodules appear as iso- or hyperintense lesions. The diagnostic accuracy of EOB-MRI for the diagnosis of early HCC is approximately 95–100% [53].…”
Section: Hypointense Signal On Hepatobiliary Phasementioning
confidence: 99%
“…According to Golfieri et al [53], during the hepatospecific phase, typical HCC and early HCC appear hypointense, whereas low-grade dysplastic or regenerative nodules appear as iso- or hyperintense lesions. The diagnostic accuracy of EOB-MRI for the diagnosis of early HCC is approximately 95–100% [53]. One third of hypovascular hypointense nodules in hepatospecific phase become hypervascular ‘progressed’ HCC, with a 1 and 3-year.…”
Section: Hypointense Signal On Hepatobiliary Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The latter has advanced to a widely recommended imaging technique based on its metabolic information with respect to the degree of enhancement in the late hepatobiliary phase [9]. This phase helps for better detection of even smaller lesions [10] and also for characterization of HCC-precursors which are expected to take up this contrast agent to different degrees compared to normal liver tissue and thus serve as a discriminator between HCC and its predecessors [11]. …”
Section: Introductionmentioning
confidence: 99%